PENDIDIKAN MORAL KIDS ZAMAN NOW DALAM PERSPEKTIF ISLAM - Syukron, Akhmad Aufa (J-PAI: Jurnal Pendidikan Agama Islam, 2018)
This paper seeks to photograph the thinking of moral education of children today in the perspective of Islam, the term children nowadays in IndonesianÂ  better known as Kids Zaman Now. Kids Zaman Now is actually a joke as well as satire refers to the "weird" or unnatural behavior of children today. moral education is a set of basic moral principles and virtues of attitudes and temperaments that must be owned and made habit by the child from the beginner until he became a mukallaf, ready to wade through the sea of life. In the modern era, the problems that arise are physical and psychological problems. Physical problems lead to human conditioning as the object of all science and technology products.This research is library research. This research collects text data. In this case the author held the collection of books, articles, internet data and journals that have relevance to the subject of the study author.Â